ChronoInsight: Automated Web Interaction Tracking and Visualization for User Experience Optimization - Aniket Y. Patil; Dr. Swapnili Karmore (International Journal of Scientific Research in Science and Technology, 2025)
Traditional web analytics tools focus mainly on high-level metrics like page visits, clicks, and session duration. These fail to capture the detailed behavioral patterns of users at the form-field level. This paper presents ChronoInsight, a lightweight, plug-and-play web analytics framework that tracks and visualizes user interactions at both page and form-field levels. ChronoInsight automatically captures user interaction data, including time spent per field and navigation sequences, and presents the results in an interactive dashboard. The system bridges the gap between conventional analytics and advanced HCI research, providing granular usability insights to optimize user experience and interface design.
Keywords: Web Analytics; User Interaction; Visualization; HCI; ChronoInsight; Usability